'Everyone assumes a man to be quite strong': Men, masculinity and rheumatoid arthritis: A case‐study approach. Issue 1 (15th October 2017) - Flurey, Caroline; White, Alan; Rodham, Karen; Kirwan, John; Noddings, Robert; Hewlett, Sarah
Abstract: Current literature has overlooked the impact of chronic illness on masculine identity. We therefore aimed to investigate the impact of rheumatoid arthritis (a long term condition, affecting more women than men) on masculine identity. Six focus groups with 22 men with rheumatoid arthritis (RA) (data reported elsewhere) followed by five one‐to‐one interviews with men (English, mean age: 59 years) sampled to reflect a heterogeneous experience of life with RA based on knowledge gained from the focus groups. Transcripts were analysed using thematic analysis and are presented as individual case studies. Whilst the case studies provide five distinct experiences, common themes can be drawn across them, such as the importance of paid work. The men needed to renegotiate their masculine identity to deal with their RA. Two dealt with this by pushing through pain to retain masculine activities, two replaced masculine roles they could no longer do with other roles, and one rejected masculinity completely. Men with long term conditions may need to re‐write their masculinity scripts to enable them to accept and adapt to their condition. However, some men struggle with this, which should be taken into consideration when designing self‐management services for men with long term conditions.